School-Based Earthquake Emergency Response Education in Bekasi - Sutarman; Arfiani Yulianti Fiyul; Neneng Sulastri (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
Although Bekasi is not classified as an area with high earthquake frequency, it remains vulnerable to the impacts of fault shifts and regional seismic activity. Low awareness and limited knowledge among the community particularly students regarding earthquake emergency response procedures can increase the risk of casualties and losses when disasters occur. This community service program aimed to enhance the preparedness of students and teachers through school-based earthquake emergency response education. The implementation methods included disaster awareness sessions, evacuation procedure training, emergency response simulations, and the establishment of evacuation routes within school environments. The program was conducted in several primary and secondary schools in the Bekasi area, involving school stakeholders, the Regional Disaster Management Agency (BPBD), and disaster relief volunteers. The results showed an 85% improvement in students’ understanding of self-rescue steps, along with the formation of school disaster response teams capable of executing evacuation procedures. This initiative is expected to serve as a sustainable education model that can be adopted by other schools in Bekasi to minimize the impact of future earthquakes.